Scanning the Ocular Albinism 1 (OA1) Gene for Polymorphisms in Congenital Nystagmus by DHPLC - Sallmann, Georgina B.; Bray, Paula J.; Rogers, Sophie; Quince, Anne; Cotton, Richard G. H.; Carden, Susan M. (Ophthalmic genetics, 2006)
Background: Nystagmus is common to all types of albinism. Some subjects with nystagmus lack convincing signs of albinism, have no other visual pathway disease, and are classified as possessing congenital idiopathic nystagmus (CN). It has been postulated that CN may be a form of ocular albinism. Methods: The presence of nystagmus, iris transillumination, and visual acuity were recorded in 39 CN and albino patients and their families. Physical characteristics were also noted. DNA from buccal swabs was obtained for use in denaturing high performance liquid chromatography (DHPLC) and chemical cleavage of mismatch (CCM) to scan several hotspots for X-linked ocular albinism (OA1) mutations. Results: Two previously reported polymorphisms were confirmed: neither was found to be a causative mutation. Conclusion: No correlation was identified between nystagmus and OA1.